Comparative Presidential's Role, Systems and Constitutional Practice Between Indonesia and South Korea - Cahyawati, Dwi Putri; Chandranegara, Ibnu Sina; Burhanuddin, Nizam; Yani, Ahmad (Faculty of Law, Universitas Jenderal Soedirman, 2023)
Indonesia and South Korea are two countries that both use a presidential system. This indicates that the two countries have something in common, especially regarding presidential institutions. But if we dive deeper, there are also differences between the two countries. But if you dive deeper, there are also differences between the two countries. This research has two research questions. What is the similarity between the presidential system in Indonesia and South Korea, and what are the differences between them. The results of the study found that although both use the presidential system of government, such a thing does not guarantee the equality of the position of the presidential institution in each country. In constitutional practice, there are variants of similarities and differences.